2016
DOI: 10.2139/ssrn.2833748
|View full text |Cite
|
Sign up to set email alerts
|

Finance for Micro, Small, and Medium-Sized Enterprises in India: Sources and Challenges

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 3 publications
(2 reference statements)
0
27
0
2
Order By: Relevance
“…Abid Hussain Committee suggested various institutional arrangements, policies and programmes for meeting long-term and short-term requirements of the smallscale industries (Hussain, 1997). A spurt of research on Indian MSMEs has taken place in the recent past on various issues such as government intervention on credit facility (Singh & Wasdani, 2016;Ayyagari et al, 2016;Das, 2015), market opportunities (Thukral et al, 2008;Sharma, 2012), skill development (Ghosh & Rajaram, 2015), cluster development (Das et al, 2007), rural and agro-enterprises (Banerjee, 2011;Aayog, 2017), economic reforms (Chakraborty & Nunnenkamp, 2008), start-ups (Sunita & Srija, 2016), innovation (Abhyankar, 2014), the impact of globalisation (Das, 2007), sickness (Goyal et al, 2012;Rastogi & Yadava, 2013), competitiveness (Mulimani et al, 2012) and technology up-gradation (Bhavani, 2011;Lahiri, 2012), etc.…”
Section: Related Workmentioning
confidence: 99%
“…Abid Hussain Committee suggested various institutional arrangements, policies and programmes for meeting long-term and short-term requirements of the smallscale industries (Hussain, 1997). A spurt of research on Indian MSMEs has taken place in the recent past on various issues such as government intervention on credit facility (Singh & Wasdani, 2016;Ayyagari et al, 2016;Das, 2015), market opportunities (Thukral et al, 2008;Sharma, 2012), skill development (Ghosh & Rajaram, 2015), cluster development (Das et al, 2007), rural and agro-enterprises (Banerjee, 2011;Aayog, 2017), economic reforms (Chakraborty & Nunnenkamp, 2008), start-ups (Sunita & Srija, 2016), innovation (Abhyankar, 2014), the impact of globalisation (Das, 2007), sickness (Goyal et al, 2012;Rastogi & Yadava, 2013), competitiveness (Mulimani et al, 2012) and technology up-gradation (Bhavani, 2011;Lahiri, 2012), etc.…”
Section: Related Workmentioning
confidence: 99%
“…According to Singh and Wasdani (2016) the primary sources of finance available to SMEs include loans from banks and non-bank financial institutions. It is however unlikely that these institutions will fully fund SMEs, especially startups, so called Greenfields, given the high financial risk associated with them and, the general unviable perception of SMEs businesses by most banks reflected in low credit ratings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surprisingly the origin and the law of funding of the capital fund is often neglected by many entrepreneurs once the business begins to operate. Singh and Wasdani (2016), established that funds for micro, small, and medium-sized enterprises (MSMEs) remains a key concern for all partners despite their lack of proper response to take responsibility of its implications. They listed personal savings, loans from friends and family, bank loans, microfinance foundations, and equity funds as the common sources of business financing.…”
Section: Sources Of Financementioning
confidence: 99%
“…An observational examination by Keasey and McGuinness (1990) showed that remotely increased fund was related to greater profit when contrasted with fund raised from within the company. However, the intrinsic constraints of formal sources of funds which has prerequisite for security or an assurance, inflexible policies, high rates of loaning, convoluted techniques, and business owners' inadequate financial knowledge of applicable schemes hinders SMEs at start-up stage from benefiting from the range of schemes targeted to assist this group of self-employers (Singh & Wasdani, 2016).…”
Section: Sources Of Financementioning
confidence: 99%